Strengthening Logical Foundation in Mathematics: A Pathway to Enhance Reasoning Skills - Hitesh Choudhury (Journal of Science and Mathematics Education, 2026)
Logical thinking serves as the backbone of understanding mathematics which helps learners to connect concepts, justify methods, and construct meaningful explanation. Many students acquire procedural competence to solve a mathematical problem but they remain unable to clearly explain the reasoning that justifies each mathematical step. This gap between performing mathematical problem and explaining solutions undermines conceptual understanding and hinders the development of higher-order reasoning abilities. This research paper addresses this issue by presenting a structured pathway for rebuilding a clear and structured logical framework for mathematics learning. This proposed framework emphasizes on deliberately integration of symbolic logic and formal inference rules into regular mathematical pedagogy. The explicit incorporation of logic within problem-solving practices helps learners to move beyond intuitive thinking toward well-justified reasoning. In support of this objective, this study presents three interrelated approaches: Reasoning Reconstruction Model (RRM), Step–Reason Mapping (SRM) and Logic-Integrated Mathematical Expression (LIME). Together, these approaches support students in structuring their thinking, aligning each solution step to logical rules and rebuilding coherent mathematical arguments.